Haloško narečje in druge diaktološke študije - Zorko, Zinka (1998)
Haloze Dialect and other Diative Studies. The Slovene language has among all slavic languages the largest number of dialects. Exploration of the Slovenian dialects begins in the first half of the 19th century with Russian experts. The greatest Slovene dialectologists: Fran Ramovš, Tine Logar and Jakob Rigler laid the foundations of dialectology on a scientific basis in the 20th century, produced two dialect maps and published some scientific works in the field of dialectology. Out of particular scientific interest, northeastern Slovenian dialects remained. In the Pannonian dialect group there was an almost untreated Haloze dialect, a poorly worked dialect in Porabje in Hungary, an unprocessed dialect in the Radgon corner in Austria. In the Styrian dialect group and in Plesje there are too few places monographically treated. To develop scientific knowledge of these dialects, work is very necessary and important.